Markers of systemic inflammation in diagnostics and in prediction of outcome of community-acquired infection - Aalto, Hannele (Helsinki University Biomedical Dissertations, ISSN 1457-8433, 2007)
Abstract in Finnish.
Keywords: Acute Disease : diagnosis; Antigens, CD14; Bacteremia : blood; Bacteremia : immunology; Biological Markers; Community-Acquired Infections : immunology; Community-Acquired Infections : mortality; Predictive Value of Tests; Patient Admission; Shock, Septic; infektiot; tulehdus; biomarkkerit; diagnostiikka